Nilai Toleransi Beragama dalam Buku Cerita Kearifan Lokal: Relevansinya bagi Pendidikan Multikultural Anak Usia Dini - Az Zahra Fitria; Lina Amelia; Yerina Elma Hastari; Syifa Febirizkia; Assaidatul Karimah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Religious tolerance is an essential value that should be introduced from an early age, especially in Indonesia as a multicultural country with diverse ethnic, cultural, and religious backgrounds. Early childhood education (ECE) has an important role in fostering tolerant attitudes through meaningful learning experiences. One effective medium is local wisdom-based storybooks, which integrate cultural values and social norms into narratives accessible to children. This study aims to analyze religious tolerance values contained in local wisdom storybooks and their relevance to multicultural education in ECE. The research uses a qualitative approach with content analysis. Data sources include Indonesian folktales such as Bawang Merah dan Bawang Putih, Malin Kundang, Si Pitung, Lutung Kasarung, and Timun Mas. Data were collected through documentation and systematic reading, then analyzed using the Miles and Huberman model involving data reduction, data display, and conclusion drawing. The findings show that these storybooks contain values of respect for differences, empathy, solidarity, cooperation, and peaceful conflict resolution. These values support multicultural education in ECE through storytelling, discussions, role-playing, and culturally responsive learning activities. The study concludes that local wisdom storybooks are authentic and culturally relevant resources for developing children’s multicultural competence and religious tolerance from an early age.